Using content-based image retrieval for accessing images on the web for children - Talib, Ahmed; Mahmuddin, Massudi; Husni, Husniza (2010)
Children are among the most frequent and important users of Internet. The children can search any type of data in any digital forms in the digital libraries, web directories, or in many other media repositories. However, one possible limitation of searching these digital artifacts is that the young children have great difficulty in writing, spelling, and explaining their ideas during Internet search (lack of query formulation); this will limit expressing their intention. Language of the Internet are English, thus imposes problem for non-native children.In addition, miss-annotation of images on the Internet could expose children to porno images and sites. Thus, this paper reviews existing search engines for children and proposes a new concept to unify and for easy searching designed for children of various languages by using image search instead of keyword search.In our proposed idea, we shall use Content Based Image Retrieval(CBIR) technique to retrieve all relevant images to image queried by a child, this is a promising approach that will remove all of the above difticulties faced by the children and protect them from get the unsuitable results. This idea is part of an on-going research to build CBIR-based Image Search Engine.